Record of Prehistoric Debris Avalanches on the North Flank of Mount St. Helens Volcano, Washington - Hausback, Brian; Swanson, Donald (Geoscience Canada, 1990)
Summary in the crater walls and deep canyons on the north flank of Mount St. Helens, dacitic volcaniclastic rocks and domes of Pine Creekage (2.5-3.0 ka and possibly older) are per-vasively deformed and contain deposits ofpossibly two debris avalanches. The base ofthe younger avalanche deposit contains numerous logs, one of which yielded an age of 2590±120 14C years B.R The Pine Creeksection is capped by slightly faulted and ésite and basalt of Castle Creek age (1.7-2.2 ka). In the northeast and northwest walls of the crater, dacite domes of Pine Creek age and older are pervasively fractured. North-dipping normal faults and low-angle thrusts cut the domes. We postulate that forceful intrusion caused the deformation and slope failure in late Pine Creek time, in a manner similar to emplacement of the bulging crypto-dome in 1980.